MODERN APPROACH TO THE TREATMENT OF CYSTIC FIBROSIS IN NEWBORNS - Latipova Sh. A. (Modern American Journals, 2026)
Cystic fibrosis is a severe inherited disorder characterized by defective chloride transport, leading to multisystem involvement primarily affecting the lungs and pancreas. Early diagnosis in newborns through newborn screening programs has significantly improved clinical outcomes by enabling timely initiation of comprehensive treatment strategies. Modern management emphasizes a multidisciplinary approach combining respiratory therapies, nutritional support, infection control, and novel pharmacological agents such as CFTR modulators. This review summarizes current advancements in the diagnosis and treatment of cystic fibrosis in neonates, highlighting the importance of early intervention to improve survival rates and quality of life.
Keywords: Cystic fibrosis; newborn screening; CFTR modulators; respiratory therapy; pancreatic enzyme replacement; multidisciplinary care; early diagnosis; neonatal management